Tocilizumab: The Key to Stop Coronavirus Disease 2019 (COVID-19)-Induced Cytokine Release Syndrome (CRS)? - Liu, Danfei; Zhang, Tongyue; Wang, Yijun; Xia, Limin (Frontiers in Medicine, 2020)
The COVID-19 disease is an unprecedented international public health emergency and considerably impacts the global economy and health service system. While awaiting the development of an effective vaccine, searching for the therapy for severe or critical COVID-19 patients is essential for reducing the mortality and alleviating the tension of the health service system. Cytokine release syndrome induced by elevated interleukin-6 was recognized to underscore the pathology of severe COVID-19 patients. Inhibiting cytokine release syndrome by agents suppressing IL-6 may relieve symptoms, shorten the hospital stay and reduce the need for oxygen therapy. Although evidence from randomized, double-blinded clinical trials is still lacking, the IL-6R inhibitor tocilizumab has shown some clinical benefits in the treatment of severe COVID-19 patients and have been included in clinical guidelines. In this review, we focused on the possible mechanisms of Tocilizumab in the treatment of cytokine release syndrome and highlighted some significant considerations in the use of Tocilizumab to treat COVID-19 patients.